Pemanfaatan Instagram Sebagai Media Promosi Jasa Tata Rias Pada Risa Vonda Make Up & Henna di Bukittinggi - Rahma Dini; Tomi Hendra (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
This research uses qualitative descriptive research. The data collection method was carried out using interviews and observation. Based on the results of research conducted regarding "Use of Instagram as a Media for Promotion of Makeup Services at Risa Vonda Make Up & Henna in Bukittinggi" it can be concluded that there are several uses made by Risa Vonda, this is in accordance with the new media theory put forward by Pierre Levy. First, the social interaction view: the existence of new media that creates space between users to interact and get information quickly because Instagram is one of the social media that can provide a great opportunity to use Instagram as a promotional medium. Second, the social integration view: the social integration view related to this research is that Instagram has become a habit for Risa's clients who follow it to get all the latest information. In this case, clients can also see photos or videos uploaded by Risa after the client uses her services. From there, we got views from clients and opinions from Risa Vonda's followers. In using Instagram media, of course, there are internal and external obstacles that Risa Vonda feels. First: Internal obstacles, namely not optimizing the Instagram Business features on Instagram, and lack of time. External obstacles are internet networks when they travel to areas where it is difficult to get internet access.